The elephant man - Vicary, Tim, 1949- (Oxford : Oxford University Press, 1992)
Story of Joseph Merrick, the Elephant Man
"First published in Oxford Bookworms: 1989."-- T.p. verso.
English stage books.
Keywords: Merrick, Joseph Carey, -- 1862-1890.; Readers; Readers for new literates; English language -- Textbooks for foreign speakers; English language -- Readers; English language -- Study and teaching; English language -- Study and teaching -- Foreign speakers; Reading comprehension -- Problems, exercises, etc; High interest-low vocabulary books; Abnormalities, Human -- Patients -- England; Proteus syndrome -- Patients -- England -- Biography; English language -- Textbooks for foreign speakers